Angiosarcoma of the Bladder: Case Report and Review of the Literature. (2008) - Williams, Steve K.; Romaguera, Rita L.; Kava, Bruce
Abstract : Our objective was to present a new case of angiosarcoma of the bladder after therapeutic radiation of the prostate, and discuss the treatment and clinical course of this rare tumor; the role of multimodality treatment is also discussed. We report a case of angiosarcoma of the bladder. Presentation, clinical course, and treatment were outlined and discussed. A MEDLINE search of all reported cases of angiosarcoma in the English language literature was performed. Thirteen previous cases of bladder angiosarcoma have been reported and three previous cases have been reported after therapeutic radiation. Hematuria was the most common presentation. Overall survival is poor, with 5-year survival rates at 35%. Longer-term survival has been demonstrated in patients who have had a multimodal approach to treatment, which combines radical surgery with chemotherapy and radiotherapy. Angiosarcoma of the bladder is a rare disease with overall poor prognosis. Optimal treatment has not been defined, but multimodality approaches appear to have a survival benefit.